Pengimplementasian Algoritma RSA Untuk Mengamankan E-mail Menggunakan Outlook dan OpenPGP - Sri Ana Margareth Nababan; Resad Setyadi (STMIK Budi Darma, 2022)
The development of technology is enough to help humans in carrying out their daily activities. With the existence of technology, humans can easily access data and information anywhere and anytime. The use of technology most often used by people is to communicate because it can connect quickly and easily. The many activities that can be carried out through technology make some people need security and confidentiality in their activities and in their communications. The RSA algorithm has 2 types of keys for security, namely the Public key and the Private key. The public key can be given to anyone while the private key can only be known by interested people. MsOutlook is software that can be used to exchange messages with other people and Open PGP is software that is equipped with cryptographic capabilities, namely encryption and decryption. Encryption is used to convert messages that were originally plaintext to ciphertext and decryption is used to translate ciphertext to plaintext. The purpose of this research is to help explain how MsOutlook and Open PGP are integrated with each other to help maintain the confidentiality of messages sent. As for the results obtained from the results of this research is to display encryption and decryption in maintaining the confidentiality of messages that have been sent by using a passphrase to access the message.